Evaluating the Effects of Long-Term Salinity Stress on the Growth and Physiology of Mono and Mixed Crops - Khulan Sharavdorj; Ser-Oddamba Byambadorj; Yeongmi Jang; Youngjik Ahn; Jin-Woong Cho (Agronomy, 2024)
Soil salinity is a key factor to limiting agricultural products throughout the world, especially in arid and semi-arid areas, since it intervenes with plant morpho-physiology, resulting in reduced growth and development, as well as disruption of ion homeostasis. This work examined the effects of salinity stress on the mono-cropping of T. pratense, F. arundinacea, and M. sativa and CaSO4 and MgSO4 on the mixed-cropping of T. pratense and F. arundinacea under saline conditions. Plants were assessed by dry weights, physiological parameters (photosynthesis rate, SPAD, SLA), forage quality, and ion concentrations. The biomass of all mono species decreased under salinity, except M. sativa, and mixed cropping was affected less than mono-cropping. The values of the mono-cropping of SPAD were decreased in the long term, and SLA was higher than the control in mixed cropping, with the photosynthesis rate of mono-cropping being higher in medium salinity in the long-term; moreover, CaSO4 and MgSO4 enhanced the photosynthesis rate of mixed cropping. Overall, we concluded that M. sativa is tolerant to medium salinity, and mixed cropping plus MgSO4 and CaSO4 were efficient under salinity stress.